Oral lesions as a clinical sign of systemic lupus erythematosus - Eliza Kristina M. Munthe; Irna Sufiawati (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Oral lesions represent one of the most important clinical symptoms of systemic lupus erythematosus (SLE), an autoimmune disease with a high degree of clinical variability rendering it difficult to arrive at a prompt and accurate diagnosis. There are many unknown causes and multiple organ systems involved, with the result that permanent organ damage may occur before treatment commences. Purpose: The purpose of this case report is to discuss the importance of recognizing the lesions related to SLE which may help dentists to make an early diagnosis. Case: A 17-year-old female patient was referred by the Internal Medicine Department with a suspected case of SLE. Prior to admittance to the hospital, the patient was diagnosed with tuberculosis. A subsequent extraoral examination revealed ulceration with a blackish crust on the upper lip. An intraoral examination showed similar ulceration covered with a blackish crust on the labial mucosa accompanied by central erythema in the hard palate. Blood tests indicated decreased levels of hemoglobin, hematocrit and platelets, but increased levels of leukocytes. A diagnosis of oral lesions associated with SLE and angioedema was formulated. Case management: The patient was given 1% hydrocortisone and vaseline album for extraoral lesions, while 0.2% chlorhexidine gluconate and 0.1% triamcinolone acetonide was used to treat intraoral lesions. An improvement in the oral lesions manifested itself after two weeks of treatment. Conclusion: Early detection of oral lesions plays a significant role in diagnosing SLE. It is important for the dentist to recognize the presentation of diseases that may be preceded by oral lesions. A multidisciplinary approach and appropriate referrals are necessary to ensure comprehensive medical and dental management of patients with SLE.